The power of personas: Exploring an innovative model for understanding stakeholder perspectives in an oncology learning health network - Dylan J. Cooper; Jessie Karten; Sarah E. Hoffe; Daniel A. King; Matthew Weiss; Danielle K. DePeralta; Andrew L. Coveler; Sunil R. Hingorani; Tracey Shefter; Cheryl Meguid; Hannah Roberts; Theodore S. Hong; et al. (Learning Health Systems)
Abstract Introduction Learning health networks (LHNs) improve clinical outcomes by applying core tenets of continuous quality improvements (QI) to reach community‐defined outcomes, data‐sharing, and empowered interdisciplinary teams including patients and caregivers. LHNs provide an ideal environment for the rapid adoption of evidence‐based guidelines and translation of research and best practices at scale. When an LHN is established, it is critical to understand the needs of all stakeholders. To accomplish this, we used ethnographic methods to develop personas of different stakeholders within The Canopy Cancer Collective, the first oncology LHN. Methods We partnered with a firm experienced in qualitative research and human‐centered design to conduct interviews with stakeholders of The Canopy Cancer Collective, a newly developed pancreatic cancer LHN. Together with the firm, we developed a personas model approach to represent the wide range of diverse perspectives among the representative stakeholders, which included care team members, patients, and caregivers. Results Thirty‐one stakeholders from all facets of pancreatic cancer care were interviewed, including 20 care team members, 8 patients, and 3 caregivers. Interview transcripts were analyzed to construct 10 personas felt to represent the broad spectrum of stakeholders within The Cancer Canopy Collective. These personas were used as a foundation for the design and development of The Cancer Canopy Cancer Collective key drivers and aims. Conclusions As LHNs continue to facilitate comprehensive approaches to patient‐centered care, interdisciplinary teams who understand each other's needs can improve Network unity and cohesion. We present the first model utilizing personas for LHNs, demonstrating this framework holds significant promise for further study. If validated, such an approach could be used as a dynamic foundation for understanding individual stakeholder needs in similar LHN ecosystems in the future.